Critical voltage, thermal buckling and frequency characteristics of a thermally affected GPL reinforced composite microdisk covered with piezoelectric actuator. Issue 4 (3rd April 2022) - Jermsittiparsert, Kittisak; Ghabussi, Aria; Forooghi, Ali; Shavalipour, Aghil; Habibi, Mostafa; won Jung, Dong; Safa, Maryam
Abstract: Due to the remarkable progress in the field of the manufacturing process, smart composites have become the desired target for high-tech engineering applications. Accordingly, for the first time, thermal buckling, critical voltage and vibration response of a thermally affected graphene nanoplatelet reinforced composite (GPLRC) microdisk in the thermal environment are explored with the aid of generalized differential quadrature method (GDQM). Also, the current microstructure is coupled with a piezoelectric actuator (PIAC). The extended form of Halpin-Tsai micromechanics is used to acquire the elasticity of the structure, whereas, the variation of thermal expansion, Poisson's ratio, and density through the thickness direction is determined by the rule of mixtures. Hamilton's principle is implemented to establish governing equations and boundary conditions of the GPLRC microdisk joint with a PIAC. The compatibility conditions are satisfied by taking perfect bonding between the core and PIAC into consideration. Maxwell's equation is employed to capture the piezoelectricity effects. The numerical results revealed the important role of distribution patterns and weight fraction of GPL ( g GPL ), non-dimensional piezoelectric thickness ( hp / h), outer to the inner ratio of the radius ( R o / R i ) and applied voltage on the frequency behavior, critical voltage and thermal buckling of the system. Another valuable consequence is that the influence of the h p parameter is hardly dependent on the value of the temperature changes ( Δ T ). The favorable suggestion of this survey is that for optimized designing of the GPLRC microsized circular plate should pay special attention to pattern 3 of the GPLs, because in this pattern by increasing the g GPL parameter the critical voltage of the structure increases but for other patterns of GPL, this phenomenon is inverse.